Beam Inc. : the dilution of the Makers Mark brand (A) - Klinger, Robert; Laughner, Tom; Macdonald, Kim; O'Rourke, James S., 1946- (London : SAGE Publications Ltd, 2017)
Makers Mark may be part of a premium spirits portfolio but maintaining its authentic history is still important to the brand. When faced with the challenge of growing demand and an insufficient supply of whiskey, the Makers Mark management team needs to decide if diluting their whiskey is the best way to meet demand.
Originally published in Klinger, R., Laughner, T., MacDonald, K., & ORourke, J. S. (2013). Beam Inc.: The dilution of the Makers Mark brand (A). 13-10 (A). Notre Dame, IN: The Eugene D. Fanning Center for Business Communication, Mendoza College of Business, University of Notre Dame.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Beam Inc; Maker's Mark Distillery; Branding (Marketing); Whiskey industry